Pemberdayaan Nasyiatul Aisyiyah Perbatasan Kalbar melalui Sabun Padat Eco Enzyme Kreatif - Sari, Wulan Purnama; Hudzaifah, Yasir; Yeni, Yeni; Rizky, Fitri Nur; Amalia, Tasya Syawa (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity was conducted in Sintang Regency by a team of lecturers and students from Muhammadiyah University of Pontianak, aimed at enhancing the knowledge and skills of Nasyiatul Aisyiyah members in utilizing eco-enzymes as a basic ingredient for making environmentally friendly solid soap. The selection of this topic is motivated by the importance of developing environmentally-based creative economies and empowering women in border areas. The methods used include Focus Group Discussion (FGD), socialization, and skill demonstrations. The results show a significant improvement in participants' understanding, evidenced by an increase in pre-test and post-test scores of 54 points in the socialization and 40 points in the training. This activity not only provides theoretical knowledge but also equips practical skills that can be applied in daily life. This program is important in supporting the achievement of SDG 8 and the economic empowerment of the community through environmentally friendly products.